Divisia monetary aggregates for a heterogeneous euro area - Maximilian C. Brill; Dieter Nautz; Lea Sieckmann (Empirica, 2020)
Since the run-up to the great recession, there has been a significant degree of heterogeneity across euro area countries both in terms of interest rates and in the composition of monetary assets. In order to account for the heterogeneity of monetary assets within and across member countries, we propose a Divisia monetary aggregate for the euro area. In line with earlier evidence obtained for the United States, our results from a panel probit analysis show that the divergence between the Divisia and the simple sum aggregate has a significant predictive content for recessions in euro area countries.
Keywords: E51; E32; C43; 330; Monetary aggregation; Euro area Divisia aggregate; Recessions